Diagnosis filariasis malayi dengan ELISA Sandwich menggunakan antibodi monokional - Soeyoko Soeyoko (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
Malayan filariasis is still the major public health problem in Indonesia. In endemic area, when microfilaremia and clinical manifestations are absent, the diagnosis of malayan filariasis is extremely important, particularly for filariasis control.With the development of hybridoma technology, it is possible to produce monoclonal antibody against any stage of Brugia malayi, which is capable of detecting the circulating parasite antigen in malayan filariasis sera.Sandwich ELISA, assay using Fab 4 monoclonal antibody could identify circulating parasite antigen in human sera. With this assay it was found that: 100% of sera from symptomatic-microfilaremic, 50% of sera from symptomatic-amicrofilaremic, 82,1% of sera from asymptomatic-microfilaremic and 24,4% of sera from asymptomatic-amicrofilaremic residents of filariasis-endemic areas positively contained circulating antigen.In comparison with the conventional method, the sensitivity and specificity of this new technique are 85,2% and 75,4% respectively.From this study it is concluded that Sandwich ELISA is proved to be very sensitive as an immunological test to detect filarial infection without any clinical manifestation or microfilaria in the blood.Key words : malayan filariasis - circulating antigen - monoclonal antibody - Sandwich ELISA - asymptomatic-amicrofilaremic.